DESIGNING AN UPPER STAGE STEERING SYSTEM FOR A FORMULA FSAE CAR - Greg WHEATLEY; Ahmed ALI (Scientific Journal of Silesian University of Technology. Series Transport)
The objective of this work is to design an upper stage steering system for the Formula FSAE car “Omega” that will effectively translate driver input force to the rack and pinion. The system consists of a steering wheel, steering shafts, universal joints, a quick release mechanism, and connection points to the car. Critical loads have been determined, and the final design has been validated using finite element analysis to ensure the safety of the assembly during normal operation and worst-scenario cases. The design key factors were performance, weight, cost, ergonomics, maintainability, manufacturability and reliability.